PENERAPAN MODEL PEMBELAJARAN LANGSUNG BERBANTUAN MEDIA VIDEO UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR SISWA - Netrisal; Bayu Insanistyo (UNIB Press, 2022)
The purpose of this research was to describe the application of direct learning model assisted by video media in order to improve students' motivation and learning achievement. Classroom action research and quasi-experimental methods. The subjects of this research were 30 students of class X TO5 of SMKN 4 Bengkulu City, while the population and samples were the students of class X TO4 as the experimental class and the students of class X TO 3 as the control class. This research used a total sample with the observation method, observation sheets on teacher’s activities in applying the direct learning and questionnaire sheets to measure the students’ motivation and a test of bottom passing skills in volleyball games to measure the students’ achievement. The obtained data were analyzed based on the type of data in which qualitative data were analyzed quantitatively by using SPSS, they were paired sample t test and independent sample. Based on the results of the research which has been carried out in three cycles, it was known that the application of the direct learning model with the video media assistance could increase students' motivation and learning achievement in PJOK subjects. And the application of the direct learning model assisted by video media was also more effective to increase the students’ achievement and motivation in PJOK subject.